Mobile Web-Based Information System for Participants "Program Keluarga Harapan” (PKH) in Sikapat Village, Sumbang, Banyumas Regency - Purnomo, Ari; Wibowo, Feri (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
The Family Hope Program (PKH) is one of the government's efforts to accelerate poverty reduction. This social protection program is known internationally as Conditional Cash Transfers (CCT). The problem found in Sikapat Village, Sumbang, Banyumas Regency is regarding the process of managing PKH participant data which uses the old system, where all requirements for getting assistance must be submitted directly to such assistants and administrators so that these requirements can be lost, resulting in many errors. Managing data for PKH program participants is repetitive and takes a long time, and data storage does not use a database. So we need an information system that is expected to help the PKH participant data management process quickly so that it is hoped that it can replace the old method with a new way, namely a computerized system based on Realtime Database (firebase) using the Javascript programming language (ReactJS) that can run on mobiles and websites.